The Effectiveness Of Corporate Governance In Preventing Tunneling Activities After Covid-19 - Jusman, Jumriaty; Tina lestari (SEAN Institute, 2024)
The purpose of this study is to determine the application of corporate governance principles affecting the prevention of tunneling activities after the COVID-19 pandemic and to determine the role of digital technology in supporting effective corporate governance to prevent tunneling activities after the pandemic. The method used in this study is a qualitative method using the literature review method. The results of this study are that the success of corporate governance regulations and policies in preventing post-pandemic tunneling will depend on collaboration between governments, regulatory agencies, companies, and other stakeholders. This collaboration is needed to create a strong governance ecosystem, where the principles of transparency, accountability, fairness, and responsibility can be consistently enforced. In addition, adaptation to changes in the global business environment and ever-evolving technology will be a determining factor in maintaining corporate integrity and protecting the interests of all stakeholders in the future.